Innovative Technologies In Nursing - Tashmatova Sh.A (American Journal of Biology and Natural Sciences, 2024)
Innovation is the process of introducing something new into various spheres of business, production and industry. With the development of medical science, the role of nursing personnel in the healthcare system is increasing. In order to care for patients, it is necessary to master increasingly complex medical and technical knowledge and acquire new skills, as well as improve those already acquired.